Toleration as recognition - Galeotti, Anna E. (Cambridge University Press, 2002)
"In this book, Anna Elisabetta Galeotti examines the most intractable problems which toleration encounters and argues that what is really at stake is not religious or moral disagreement but the unequal status of different social groups. Liberal theories of toleration fail to grasp this and consequently come up with normative solutions that are inadequate when confronted with controversial cases. Galeotti proposes, as an alternative, toleration as recognition, which addresses the problem of according equal respect to groups as well as equal liberty to individuals. She offers an interpretation that is both a revision and an expansion of liberal theory, in which toleration constitutes an important component not only of a theory of justice, but also of the politics of identity. Her study will appeal to a wide range of readers in political philosophy, political theory, and law."--Jacket